Misuse of "Power" and other mechanical terms in sport and exercise science research - Winter, E. M.; Abt, G.; Brookes, F.B.C.; Challis, J. H.; Fowler, N. E.; Knudson, D. V.; Knuttgen, H. G.; Kraemer, W. J.; Lane, A. M.; Mechelen, W. van, Morton, R. H.; Newton, R. U.; Williams, C.; et al. (The Journal of Strength and Conditioning Research, 2016)
Despite the Système International d'Unitès (SI) that was published in 1960, there continues to be widespread misuse of the terms and nomenclature of mechanics in descriptions of exercise performance. Misuse applies principally to failure to distinguish between mass and weight, velocity and speed, and especially the terms "work" and "power." These terms are incorrectly applied across the spectrum from high-intensity short-duration to long-duration endurance exercise. This review identifies these misapplications and proposes solutions. Solutions include adoption of the term "intensity" in descriptions and categorizations of challenge imposed on an individual as they perform exercise, followed by correct use of SI terms and units appropriate to the specific kind of exercise performed. Such adoption must occur by authors and reviewers of sport and exercise research reports to satisfy the principles and practices of science and for the field to advance.